PANCREATIC NEUROENDOCRINE TUMORS: SURGICAL RESECTION - Marcos BELOTTO; Bruna do Nascimento Santos CROUZILLARD; Karla de Oliveira ARAUJO; Renata D’Alpino PEIXOTO (ABCD: Arquivos Brasileiros de Cirurgia Digestiva, 2019)
ABSTRACT Introduction: Pancreatic neuroendocrine tumors (pNET) correspond to about 3% of all tumors in pancreas and could be presented as a difficult diagnosis and management. Objective: To review the diagnosis and treatment of the pNET available in scientific literature. Method: A bibliographic survey was performed by means of an online survey of MeSH terms in the Pubmed database. A total of 104 articles were published in the last 15 years, of which 23 were selected as the basis for the writing of this article. Results: pNET is an infrequent neoplasia and their incidence, in USA, is about 1:100.000 inhabitants/year. Thereabout 30% of them produce hormones presenting as a symptomatic disease and others 70% of the cases could be silent disease. Magnetic Resonance Imaging (MRI) and/or Computed Tomography (CT) have similar sensitivy to detect pNET. They are very important when associated to nuclear medicine mainly Positron Emission Tomography (PET-CT) Gallium-68 to find primary tumor and its staging. The appropriate treatment should be chosen based on characteristics of the tumor, its staging and associated comorbidities. Conclusion: The surgical resection is still the best treatment for patients with ressectable pancreatic NETs. However, the size, grade, tumor functionality, stage and association with multiple endocrine neoplasia type 1 (MEN-1) are important to define who will be eligible for surgical treatment. In general, tumors bigger than 2 cm are eligible for surgical treatment, except insulinomas whose surgical resection is recommended no matter the size.